2011
DOI: 10.1177/1545968311416822
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Truncal Exercises Early After Stroke to Improve Balance and Mobility

Abstract: In addition to conventional therapy, truncal exercises have a beneficial effect on truncal function, standing balance, and mobility in people after stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
129
0
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(146 citation statements)
references
References 42 publications
5
129
0
12
Order By: Relevance
“…There were no score changes found in static sitting balance subscale, because the subjects in this study were able to maintain independent sitting posture for more than 10 seconds. Saeys et al (2012) reported that improved trunk control has a carry over effect on dynamic balance after trunk control training, and that the trunk stability is essential for limb movements. The results of TUG also showed a significant improvement in the WST group compared to the control group in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no score changes found in static sitting balance subscale, because the subjects in this study were able to maintain independent sitting posture for more than 10 seconds. Saeys et al (2012) reported that improved trunk control has a carry over effect on dynamic balance after trunk control training, and that the trunk stability is essential for limb movements. The results of TUG also showed a significant improvement in the WST group compared to the control group in this study.…”
Section: Discussionmentioning
confidence: 99%
“…According to several studies, trunk control ability can be improved by performing specific exercise training (Howe et al 2005;Verheyden et al 2007;Saeys et al 2012). A study by Verheyden et al (2009) showed that 10 hours of additional trunk exercises improved the ability to control the trunk in subacute stroke patients, and reaching exercises performed while seated were reported to improve sitting balance, peak vertical force on the paretic foot, and gait speed in chronic hemiplegic patients (Dean et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Kelumpuhan fisik pasca Stroke disebabkan oleh gangguan postural tubuh yang dapat mempengaruhi keseimbangan, kemampuan berjalan dan meningkatkan risiko jatuh klien serta gangguan aktivitas fungsional sehari-hari yang terkait dengan peran vital fungsi ekstremitas atas. (Weerdesteyn et al 2008;Saeys et al 2012;Aprile et al 2006;Wee et al 2015). Truncal control exercise memperbaiki dan memelihara postural tubuh yang baik dalam melakukan gerak serta menjadi dasar untuk semua gerakan pada lengan dan tungkai.…”
Section: Pendahuluanunclassified
“…They found significant improvement in dynamic sitting balance and trunk coordination. Furthermore, their study showed that truncal function improved postural control during standing balance and mobility indicating the importance of truncal exercises in the rehabilitation of stroke patients [26].The improvement in the trunk lateral flexion ROM in the control group could be due to the effect of regular or intensive training as the participants were asked to bend their trunk laterally to touch the exercise table with elbow & return to the initial position. In addition, exercises that were implemented for the control group was focused on coordination, selective muscle strengthening and selective movements of the trunk.…”
Section: Control Groupmentioning
confidence: 99%
“…The exercises in sitting were as follows: flexion and extension of the trunk (the participant were asked to flexed and extends the trunk without moving the trunk forward or backward);trunk lateral flexion initiated from the shoulder and pelvic girdle (from the shoulder girdle means -participant touches the plinth with one elbow and returns to the starting position, from the pelvic girdle means-participant lifts one side of the pelvis and returns to the starting position); rotation from the upper part of trunk (from the upper part of the trunk means-participant moves each shoulder forward and backward); rotation from the lower part of the trunk (from the lower part of the trunk means-participant moves each knee forward and backward); and shuffling the pelvis forward, backward and one side to other on a plinth.The truncal exercises were performed with the assistance initially if required and progressed to a state of no assistance. The therapist based on the participant"s performance determined the numbers of repetitions of the exercise [25][26][27].…”
Section: Interventionmentioning
confidence: 99%